Christ-faith and Abraham in Galatians 3-4: Paul's tale of two siblings - Harris, Johnathan F. (Biblical interpretation series, 2023)
"On what basis are Gentile Christians justified and full inheriting members of Abraham's family? By being circumcised and keeping the Torah? Paul answers by reinterpreting the Abraham narrative in light of the Christ-event as a story of two siblings. True Abrahamic children are those whose Spirit-wrought life arises, as God promised Abraham, from the event of Christ-faith. Like Isaac, they receive the life-giving power of the Spirit that is tethered to God's promise and the event of eschatological faith. By contrast, those who, like Ishmael, are related to Abraham only by means of the flesh are slaves and not heirs"--